Impact of Diversification Strategies on Multinational Firms’ Performance in Zambia’s Food Sector - Bwembya, Raymond Chongo; Kachamba, Norman (International Journal of Engineering and Management Research, 2025)
This study investigates the impact of diversification strategies on the performance of multinational firms within Zambia’s food sector. Drawing from four types of diversification strategies—vertical, horizontal, concentric, and conglomerate—the study employs a descriptive survey approach and multiple regression analysis. Results demonstrate that horizontal and concentric diversification strategies significantly enhance firm performance, explaining 45.6% of its variation. The study concludes that carefully aligned diversification can provide competitive advantage and improve financial performance, especially in developing markets with volatile operating environments.